Effect of Emotional Intelligence and Adaptation Ability on Employee Engagement Hotel Amaris Tasikmalaya - Fenti Hardianti (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This research was conducted with the aim of knowing the effect of Emotional Intelligence and Adaptability on Employee Engagement Hotel Amaris Tasikmalaya. The method used in this research is a case study method using data obtained directly through questionnaires distributed to 32 respondents who are non-manager employees of Amaris Hotel Tasikmalaya. The technique used in this research is multiple linear regression analysis. Based on the results of the study, it can be seen that Emotional Intelligence partially has a significant effect on Employee Engagement, partially Adaptable Ability has a significant effect on Employee Engagement, simultaneously Emotional Intelligence and Adaptability have a significant effect on Employee Engagement Hotel Amaris Tasikmalaya.